Pengembangan Media Pembelajaran Kubus Huruf Pada Materi Pengenalan Huruf Abjad Anak Usia Dini Untuk Meningkatkan Keaktifan Siswa KB B Al- Ikhlas Grabagan - Fashi Hatul Lisaniyah; Yulfira Fajarini Agustina; Ummidlatus Salamah (Alzam: Journal of Islamic Early Childhood Education, 2024)
Development of Letter Cube Learning Media in Early Childhood Alphabet Letter Introduction Material to increase the learning activity of KB B Al-Ikhlas Grabagan students. So that later it becomes a learning medium that has positive value for students in increasing their activity in playing while learning. This letter cube learning media is designed to be as attractive as possible and is equipped with illustrated flash cards which aim to increase students' activeness in learning to recognize letters. And it can motivate educators in their ability to develop learning variations through the alphabet letter cube learning media so as to create fun learning for students. So the activity level at the age of 3-4 years is also not well developed. Based on the problem formulation, namely: What is the level of validity, practicality and effectiveness of the letter cube media with the aim of describing the level of validity, feasibility, practicality and effectiveness of the letter cube media. The type of research used is research and development using the 4-D development model, but the author only carried out three stages, namely the definition, design and development stages. The types of data collection instruments used are validation sheets, practicality sheets, and effectiveness sheets. From this research (1) Expert validation, the material expert validation results were 92.5% in the very valid category. Meanwhile, the media expert validation results were 86% in the very valid category. (2) The practical teacher response questionnaire results were 93.3% in the very practical category, while the student response questionnaire results were 93% in the very practical category. (3) The effectiveness test from the results of the observation sheet obtained an increase in score of 0.7 in the high category from an initial average score of 41.8% to a final average score of 82.5% from 12 students in the effective category. This proves that students experienced improvement after the Gain Normality Test was carried out.